Applying the Maternal Near Miss Approach for the Evaluation of Quality of Obstetric Care: A Worked Example from a Multicenter Surveillance Study. (23rd July 2014) - Haddad, Samira Maerrawi; Cecatti, Jose Guilherme; Souza, Joao Paulo; Sousa, Maria Helena; Parpinelli, Mary Angela; Costa, Maria Laura; Pacagnella, Rodolfo C.; Brum, Ione R.; Moraes Filho, Olímpio B.; Feitosa, Francisco E.; Menezes, Carlos A.; Guanabara, Everardo M.; et al.
Abstract : Objective . To assess quality of care of women with severe maternal morbidity and to identify associated factors. Method . This is a national multicenter cross-sectional study performing surveillance for severe maternal morbidity, using the World Health Organization criteria. The expected number of maternal deaths was calculated with the maternal severity index (MSI) based on the severity of complication, and the standardized mortality ratio (SMR) for each center was estimated. Analyses on the adequacy of care were performed. Results . 17 hospitals were classified as providing adequate and 10 as nonadequate care. Besides almost twofold increase in maternal mortality ratio, the main factors associated with nonadequate performance were geographic difficulty in accessing health services (P < 0.001 ), delays related to quality of medical care (P = 0.012 ), absence of blood derivatives (P = 0.013 ), difficulties of communication between health services (P = 0.004 ), and any delay during the whole process (P = 0.039 ). Conclusions . This is an example of how evaluation of the performance of health services is possible, using a benchmarking tool specific to Obstetrics. In this study the MSI was a useful tool for identifying differences in maternal mortality ratios and factors associated with nonadequate performance of care.